المخاطر المهنية وتأثيرها على العاملين في عيادات طب الأسنان بمنطقة أبي سليم (Comprehensive Journal of Science, 2025)
The study aimed to identify occupational hazards and their impact on workers in dental clinics. The study sample consisted of (166) participants, and the descriptive-analytical method was adopted. A questionnaire was used to collect data from the study sample.The study reached the following results:-The level of occupational hazards to which workers in dental clinics in the Abu Salim area are exposed was found to be moderate.-The level of occupational safety procedures in dental clinics in the Abu Salim area was found to be high.-There were statistically significant differences at the (0.05) level in the impact of occupational hazards on workers in dental clinics in Abu Salim in its two dimensions (occupational hazards – occupational safety procedures) according to gender, in favor of males.-There were statistically significant differences at the (0.05) level in the impact of occupational hazards on workers in dental clinics in Abu Salim in its two dimensions (occupational hazards – occupational safety procedures) according to years of experience, in favor of those with (10 years or more) of experience.-There were statistically significant differences at the (0.05) level in the impact of occupational hazards on workers in dental clinics in Abu Salim in its two dimensions (occupational hazards – occupational safety procedures) according to training courses, in favor of those who received training.
Keywords: Occupational hazards, Dental clinics, Workers..